Interferometric Migration and Modeling in VSP Configuration: Synthesizing Virtual Functions for Reflector Imaging: Modelado y Migración Interferométrica en Configuración VSP: Síntesis de Funciones Virtuales y Reconstrucción de Reflectores (BISTUA Revista de la Facultad de Ciencias Básicas, 2025)
Seismic interferometry is a technique that reconstructs subsurface images by cross-correlating seismic traces, leveraging the principles of acoustic wave interference propagating through the Earth. This approach generates virtual Green's functions between pairs of receivers, enabling the estimation of elastic properties and the morphology of subsurface layers. In reservoir exploration, obtaining high-resolution and accurate images is essential for geological interpretation and decision-making. Unlike traditional seismic methods, interferometry offers advantages such as reduced sensitivity to wavefield diffusivity and environmental noise. In this study, we present a numerical modeling of interferometric migration applied to synthetic geological structures, using a vertical seismic profile (VSP) configuration.